ANALISIS POTENSI FINANCIAL DISTRESS PADA PT CENTRAL PROTEINA PRIMA, TBK - DS, Yudha Mahrom (MOTIVASI, 2019)
Purpose - This research is formulated to analyze the use of Altman Z-score Method, Springate and Fulmer to See the Potential of Financial Distress occurrence at pt Central Proteina Prima, Tbk. This research is aimed at figuring out the use of Altman Z-score Method, Springate and Fulmer to See the Potential of Financial Distress Occurrence at PT Central Proteina PrimaDesign/methodology - This research was such a descriptive research in line with the condition of the occurrence of Financial Distress at PT Central Proteina Prima, Tbk. The data used in this research was secondary data. To collect the data, the researcher used documentation technique. This research was such a quantitative analysis Findings – The results of this research showed that the Financial performance of PT Central Proteina Prima, Tbk by using Altman Z-score method was two years classified into the grei area while Springate and Fulmer method of thecompany was classified into annual Financial Distress.